AHP-DEMATEL Based Research on the Influencing Factors of the Daily Maintenance Costs of China's National and Provincial Trunk Highways - Muzammal Mehmood; Zhang BaoJing (International Journal of Engineering and Management Research, 2021)
Highway maintenance is equally crucial across borders; this paper first conducts statistics and case study research on daily federal and provincial highway maintenance costs in China's principal influencing factors. Finally, it looks at those results with the tools of AHP-DEMAT. Yet, the overall degree of influence of each factor of influence is collected to classify the significant influence factors. The results found that: the main factors influencing the daily maintenance costs of national and provincial trunk highways are: highway grade, traffic flow, service life, structure type, topography, pavement thickness, and pavement width; the influence of climate factors on costs can be adequately considered when formulating standards for daily maintenance costs for provinces/regions with a broad geographic range.